An operational high temperature thermal energy storage system using magnesium iron hydride. (11th November 2021) - Poupin, Lucas; Humphries, Terry D.; Paskevicius, Mark; Buckley, Craig E.
Abstract: Metal hydrides have been demonstrated as energy storage materials for thermal battery applications. This is due to the high energy density associated with the reversible thermochemical reaction between metals and hydrogen. Magnesium iron hydride (Mg2 FeH6 ) is one such material that has been identified as a thermal energy storage material due to its reversible hydrogenation reaction at temperatures between 400 and 600 °C. This study demonstates an automated thermal battery prototype containing 900 g of Mg2 FeH6 as the thermal energy storage material with pressurised water acting as the heat transfer fluid to charge and discharge the battery. The operating conditions of the system were optimised by assessing the ideal operating temperature, flow rate of the heat transfer fluid, and hydrogen pressures. Overall, excellent cyclic energy storage reversibility was demonstrated between 410 and 450 °C with a maximum energy capacity of 1650 kJ which is 87% of the theoretical value (1890 kJ). Graphical abstract: Image 1 Highlights: A prototype thermal battery was developed using Mg2 FeH6 as the thermal energy storage material. The automated battery consisted of a heat transfer fluid system to charge and discharge the material. Complete optimisation of the operating conditions of the system was established. Excellent cycle reversibility was demonstrated between 410 and 450 °C.